Konsep Ma’rifatullah dalam Kitab Umm Al-Barahain Karya Imam Sanusi: Analisis Inti Pendidikan Akidah - Sarah Ulfah (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2022)
The problems of akidah that arise are one of the impacts of not maximizing akidah education in Indonesia. The akidah education offered so far is a creed that focuses on (dogmatic) acceptance only. That Allah exists, the qur’an is true and everything must be accepted with trust and faith. In fact, when viewed from the object of the study of faith (akidah), it is included in the philosophical paradigm which demands rational arguments to strengthen faith so that it is not just taqlid. Problems such as surrendering to taqlid without adhering to the arguments that are in accordance with the teachings of the qur’an - namely conducting investigations by using reason - coupled with not mastering the correct creed because a lack of understanding and attention can lead to deviations and not infrequently even against the true creed. The problems above appear as implications rather than not being ma'rifatullah. Whereas in faith education, ma'rifatullah is the core of teaching that must be achieved. Looking at the phenomena that have been stated above, the author feels that this topic is very important to study and hopes that this paper will become a dedication to readers and academics so that the study of faith in Indonesian education can be given more attention so that it can achieve its core and objectives, namely ma'rifatullah The results of this study indicate that what is meant by the obligation of ma'rifatullah in Umm al-barahain Imam Sanusi is ma'rifah towards the attributes of Allah and all divine laws, not ma'rifah towards His essence and His essence because there is nothing know both. And a person is said to be ma'rifah when he fulfills the three characteristics of ma'rifah, namely jazm (belief with firm belief) in accordance with the truth and this belief must be accompanied by rational arguments.